THE EFFECTIVENESS OF WHISPERING GAME TO STUDENTS’ LISTENING SKILL - Juwita Boneka Sinaga (Universitas Riau Kepulauan, 2017)
In this research We will find the problem in learning process in the class especially in listening laboratory. The problems are the students do not know what is the meaning of what are they listening from the conversation or the teachers explanation. This research has purpose to students’ listening skill by using whispering game at second semester English Department UNRIKA academic Year 2016/2017. This research is quantitative research. The researcher used total sampling. The experimental class was taught byusing whispering game, whereas the control class was taught using lecturing method. In this research, the researcher gave 20 of questions in multiple choices form. The result of analysis can be concluded that there was significant effect. It was showed (3,01 2,01) so was rejected and was accepted. The result of analysis can be concluded that the use of whispering game at Second semester UNRIKA in academic Year 2016/2017 gave significant effect in the students’ activity in learning process than the use of close procedure.